Pengaruh Kompetensi Auditor, Independensi Auditor dan Skeptisme Profesional Auditor terhadap Pemberian Opini Audit - Prihasti Nur Amalia; Maidani Maidani; Cris Kuntadi (Peneliti.net, 2023)
Literature Review of the Influence of Auditor Competence, Auditor Independence, and Auditor Professional Skepticism on Giving Audit Opinions is a scientific article that has the aim of developing research hypotheses of influence between variables to be used in further research. The results of this literature review are: (1) The Effect of Auditor Competence on Giving Audit Opinions, (2) The Effect of Auditor Independence on Giving Audit Opinions. and (3) The Effect of Professional Skepticism on Giving Audit Opinions.